Religious Diversity and Trust in India: A Field Experiment - Al Fahoum, Reema (2012)
This paper investigates whether India’s diverse religious composition is related with mistrust between its two main religious communities namely; Hindus and Muslims. A field experiment has been undertaken which plays a trust game between urban Muslims and Hindus in Mumbai, India. This study confirms in-group biases which can be identified through lower offers between people from different religious groups. There is a difference in the trust and trustworthiness of proposers and responders based on the religion of the co-players they respond to. The study indicates that Hindus not only have greater trust and expectations of other individuals’ trust than Muslims but also feel that people from other groups are more ethnocentric.